Antibody persistence following meningococcal ACWY conjugate vaccine licensed in the European Union by age group and vaccine. (2nd August 2020) - Luo, Weichang; Arkwright, Peter D.; Borrow, Ray
ABSTRACT: Introduction: Meningococcal disease caused by Neisseria meningitidis is a major cause of meningitis and septicemia with high rates of morbidity and mortality worldwide. MenACWY-TT and MenACWY-CRM197 are meningococcal conjugate vaccines approved for use in children and adults in the UK. The aim of this review was to evaluate and compare antibody responses and persistence in different age groups after MenACWY-TT and MenACWY-CRM197 . Areas covered: Randomized trials showed that MenACWY-TT is immunogenic at all ages. MenACWY-CRM197 is immunogenic for infants and adults, but there is a lack of data for children aged 1 to 2 years. Studies on MenACWY-TT indicated that serum bactericidal antibody (SBA) utilizing baby rabbit complement (rSBA) titers were significantly higher and more stable than SBA using human complement (hSBA) titers, compared with hSBA titers, which were lower and declined more rapidly by 1 year following post-primary MenACWY-TT and MenACWY-CRM197 vaccination, especially for MenA. Expert opinion: MenACWY-TT and MenACWY-CRM197 are both well tolerated and induce similar antibody persistence and immunogenicity against all four serogroups for individuals more than one year old. rSBA assay is a more robust assay than the hSBA assay when vaccinating with MenACWY-TT, while rSBA and hSBA assays had similar antibody persistence when vaccinating with MenACWY-CRM197 .